Aggravation of spinal cord compromise following new osteoporotic vertebral compression fracture prevented by teriparatide in patients with surgical contraindications. Issue 11 (November 2016) - Zhao, Y.; Xue, R.; Shi, N.; Xue, Y.; Zong, Y.; Lin, W.; Pei, B.; Sun, C.; Fan, R.; Jiang, Y.
Abstract Summary Patients with spinal cord deficits following new unstable osteoporotic compression fracture and surgical contraindications were considered to receive conservative treatment. Teriparatide was better than alendronate at improving bone mineral density and bone turnover parameters, as well as preventing aggravation of spinal cord compromise. Introduction This study compared the preventive effects of teriparatide and alendronate on aggravation of spinal cord compromise following new unstable osteoporotic vertebral compression fracture (OVCF) in patients with surgical contraindications. Methods This was a 12-month, randomized, open-label study of teriparatide versus alendronate in 49 patients with new unstable OVCF and surgical contraindications. Neurological function was evaluated using modified Japanese Orthopedic Association (mJOA) score (11-point scale, the maximum score of 11 implies normalcy). Visual analog scale (VAS) scores, kyphotic angles, anterior-border heights and diameters of the spinal canal of the fractured vertebrae, any incident of new OVCFs (onset of OVCF during follow-up), spine bone mineral density (BMD), and serum markers of bone resorption and bone formation were also examined at baseline and 1, 3, 6, and 12 months after initiation of the medication regimen. Results At 12 months, mean mJOA score had improved in the teriparatide group and decreased in the alendronate group. Mean concentrations of bone formation and bone resorption biomarkers, mean spine BMD, and mean anterior-border height and spinal canal diameter of the fractured vertebrae were significantly greater in the teriparatide group than in the alendronate group. Mean VAS score, mean kyphotic angle of the fractured vertebrae, and incidence of new OVCFs were significantly smaller in the teriparatide group than in the alendronate group. Conclusions In patients with neurological deficits following new unstable OVCF and with surgical contraindications, teriparatide was better than alendronate at improving the BMD and the bone turnover parameters, as well as preventing aggravation of spinal cord compromise.